The Parallels between Reiki Therapy and the Tangent Paradigms of Traditional Chinese Medicine: Review of Literature - Daniel Chagas de Pontes; Vitor Hugo Auzier Lima; Dhiego Lima Costa; Daniele Salgado de Sousa; Rebeson Moraes; Matheus Pinheiro (Archives of Current Research International, 2018)
This review aims to demonstrate the similarities between Reiki therapy and traditional Chinese medicine, both in relation to its paradigm, ancient history, the concept of energy and philosophical foundations. And in conclusion, it was ratified that there are many idiosyncrasies between Reiki therapy and traditional Chinese medicine, as well as in the physiological foundations of both. This was conceived during the preparation of the monograph of the specialization in Acupuncture of Einstein College - FACEI.